'He is ruler over all' – Man and 'his' universe at the 1539 Ghent refreynen contest. Issue 1 (23rd January 2018) - Buys, Ruben
Abstract: In 1539, nineteen chambers of rhetoric presented their refereynen int vroede at the famous rhetorician's contest of Ghent. Taken together, these poems, printed that same year, provide a series of closely related perspectives on humankind, human nature, and the world and its wonders. In general they consider man to be the most powerful of all creatures, as only he (interestingly, in some cases more specifically she ) is able to overcome any worldly danger, temptation, or challenge. However, true dominance over the world is only possible if man meets specific conditions, set by God and nature – above all: rationality, piety, and a readiness to subdue one's inner world of desires and self‐conceit. Thus, the poems present various ideal types of the human self. This contribution analyzes those perspectives on humankind and the way in which the basic theme of human mastery of the world is integrated into the content as well as the structure of the refreynen . The essay also situates these refreynen in the broader context of vernacular philosophy and vernacular learning in the late medieval and early modern Low Countries.